Omicron COVID-19 variant outcomes and vaccination in non-severe and non-critical patients at admission - Zhao, Hong; Ye, Wenyi; Yu, Xia; Shi, Yu; Sheng, Jifang (Frontiers in Public Health, 2023)
The clinical data of patients infected with the Omicron variant virus in Zhejiang Province from January to 14 May 2022 were collected retrospectively. We analyzed the differences in symptoms, clinical categories of COVID-19, length of hospital stay, and time for clearance of Omicron variant viral RNA in the sputum among the groups receiving a different number of vaccine doses. The analysis showed that as the number of vaccine doses increased, the frequency of clinical symptoms, such as fever and fatigue, decreased and the frequency of patients with moderate infections gradually decreased. At the same time, the length of hospital stay was significantly shortened. Based on the multivariate analysis, one vaccine dose [odds ratio (OR): 0.21, 95% confidence interval (CI): 0.08–0.56, p = 0.002], two vaccine doses (OR: 0.54, 95% CI: 0.33–0.88, p = 0.013), and three vaccine doses (OR: 0.40, 95% CI: 0.24–0.64, p < 0.001) shortened the length of hospitalization than those with no vaccination. The persistence of the virus in the sputum was significantly shortened with one vaccine dose (OR: 0.36, 95% CI: 0.15–0.89, p = 0.027), two vaccine doses (OR: 0.46, 95% CI: 0.27–0.78, p = 0.004), and three vaccine doses (OR: 0.38, 95% CI: 0.22–0.64, p < 0.001) than those with no vaccination. Therefore, we concluded that vaccination was an effective way to protect people against infection with the Omicron variant. Indeed, on the premise of the current routine recommendation of vaccination, three vaccines were necessary for people to be protected against the Omicron variant.